Coproantigen detection of Echinococcus granulosus sensu stricto in experimentally infected dogs by in-house sandwich ELISA using crude and recombinant antigens - Celik, Figen; Selcuk, Muhammed Ahmed; Uslug, Muhammet; Simsek, Sami (Elsevier, 2026)
Dogs are the definitive hosts of Echinococcus granulosus sensu stricto (s.s.), the causative agent of cystic echinococcosis (CE) in livestock and humans. As canine infections are usually asymptomatic, early and reliable detection of active adult infections is essential for effective control and surveillance. In this study, two in-house sandwich ELISA assays were developed using purified polyclonal rabbit antibodies raised against E. granulosus s.s. soluble crude antigen (EgSCA) and a recombinant fibronectin antigen (rEgFN162). Experimental infection was established in two dogs (n = 2) by oral administration of viable protoscoleces, while one dog was maintained as a non-infected negative control. Fecal samples were collected throughout the infection period and following anthelmintic treatment. Cross-reactivity was assessed using fecal samples from dogs naturally infected with Toxocara canis (n = 5) and Ancylostoma caninum (n = 2). The diagnostic performance of both assays was evaluated in terms of timing of positivity, sensitivity, specificity, and cross-reactivity. The EgSCA-based sandwich ELISA detected coproantigens as early as 4-5 days post-infection and showed an overall sensitivity of 80% and specificity of 86.7%, with limited cross-reactivity with T. canis (20%) and A. caninum (50%). In contrast, the rEgFN162-based assay showed delayed positivity (18-23 days post-infection), lower sensitivity (46.7%), but higher specificity (93.3%). In both in-house sandwich ELISAs, coproantigen positivity persisted for an extended period after anthelmintic treatment, indicating prolonged antigen detectability despite parasite elimination. Western blot and indirect ELISA confirmed strong antigen-specific humoral responses against both antigens in immunized rabbits. Overall, the findings of this proof-of-concept study suggest that the EgSCA-based in-house sandwich ELISA is more suitable for early coproantigen-based detection of active E. granulosus s.s. infections in dogs, while rEgFN162 may serve as a complementary or confirmatory antigen in combined diagnostic approaches, contributing to improved CE surveillance and control in endemic areas.
Keywords: Cystic Echinococcosis; Echinococcus Granulosus Sensu Stricto; Coproantigen; Sandwich Elisa; Dog; Experimental Infection; Diagnosis